Acute stroke care during the first phase of COVID‐19 pandemic in Norway - Kristoffersen, Espen Saxhaug (Acta Neurol Scand, 2021)
OBJECTIVES: The aim of the present study was to investigate how the initial phase of the COVID‐19 pandemic affected the hospital stroke management and research in Norway. MATERIALS AND METHODS: All neurological departments with a Stroke Unit in Norway (n = 17) were invited to participate in a questionnaire survey. The study focused on the first lockdown period, and all questions were thus answered in regard to the period between 12 March and 15 April 2020. RESULTS: The responder rate was 94% (16/17). Eighty‐one % (13/16) reported that the pandemic affected their department, and 63% (10/16) changed their stroke care pathways. The number of new acute admissions in terms of both strokes and stroke mimics decreased at all 16 departments. Fewer patients received thrombolysis and endovascular treatment, and multidisciplinary stroke rehabilitation services were less available. The mandatory 3 months of follow‐up of stroke patients was postponed at 73% of the hospitals. All departments conducting stroke research reported a stop in ongoing projects. CONCLUSION: In Norway, hospital‐based stroke care and research were impacted during the initial phase of the COVID‐19 pandemic, with likely repercussions for patient care and outcomes. In the future, stroke departments will require contingency plans in order to protect the entire stroke treatment chain.